1993
DOI: 10.1007/bf00168050
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for the force and energetics in competitive running

Abstract: A simple mathematical model for competitive running is developed. This model contains the force and energy reserves as key variables and it described their relationship and dynamics. It is made up of three submodels for the biomechanics of running the energetics and the optimization. The model for the energetics is an extension of the hydraulic model of Margaria and Morton. The key geometric parameters of this piecewise linear, three compartment model are determined on the basis of well known physiological fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…I have traced the development of whole-body bioenergetic models over the last 50 years, from the early simple 2-component ideas of Monod and Scherrer (1965) and Lloyd (1966) and others; through Margaria (1976) and Morton's (1986a, b) 3-component extensions; to the more complex recent models of Behncke (1993Behncke ( , 1997, Ward-Smith (1985a, b) and Harman (2002). It is useful now to view the current situation in summary with reference back to the ten assumptions of the original CP model (Origins, assumptions and development and Questioning the assumptions).…”
Section: Conclusion and Further Considerationsmentioning
confidence: 98%
See 1 more Smart Citation
“…I have traced the development of whole-body bioenergetic models over the last 50 years, from the early simple 2-component ideas of Monod and Scherrer (1965) and Lloyd (1966) and others; through Margaria (1976) and Morton's (1986a, b) 3-component extensions; to the more complex recent models of Behncke (1993Behncke ( , 1997, Ward-Smith (1985a, b) and Harman (2002). It is useful now to view the current situation in summary with reference back to the ten assumptions of the original CP model (Origins, assumptions and development and Questioning the assumptions).…”
Section: Conclusion and Further Considerationsmentioning
confidence: 98%
“…Changes in VO 2 dynamics forecast by the model as a result of such structural change may provide clues. Behncke (1993) has incorporated the M-M model as one submodel in a larger mathematical model for the force and energetics of competitive running. The other submodels include the biomechanics of running and an optimisation determination.…”
Section: Applications and Developments Of The 3-component Hydraulic Mmentioning
confidence: 99%
“…Problem 1. Let (θ(t; K), L(t, K)) be the solution of the system (4) with (6). Find K * and the smallest time t * > 0 satisfying θ(t * , K * ) = α, L(t * , K * ) = 1.…”
Section: Model Statement and Motivationmentioning
confidence: 99%
“…It is based on energy conservation and the fundamental principal of dynamics. With his simple model, and relying on constant maximal oxygen uptake (constantV O2), he found that he could nevertheless reasonably predict the time of world records for distances bigger than 400 m. Several improvements of Keller's model have been introduced: the effect of fatigue [18,8], the variation in maximal oxygen uptake [2], air resistance and altitude [13]. Other related works include [17,9,10,12].…”
Section: Introductionmentioning
confidence: 99%